2019
DOI: 10.1161/atvbaha.119.312826
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-to-Mesenchymal Transition in Human Adipose Tissue Vasculature Alters the Particulate Secretome and Induces Endothelial Dysfunction

Abstract: Objective: Endothelial cells (EC) in obese adipose tissue (AT) are exposed to a chronic proinflammatory environment that may induce a mesenchymal-like phenotype and altered function. The objective of this study was to establish whether endothelial-to-mesenchymal transition (EndoMT) is present in human AT in obesity and to investigate the effect of such transition on endothelial function and the endothelial particulate secretome represented by extracellular vesicles (EV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…Furthermore, via VE-cadherin lineage tracing in mice, EndMT was also shown to be involved in the transformation of ECs into white and brown fat cells (Tran et al, 2012). Recent manuscripts identified that microvascular ECs within adipose tissue in patients with obesity undergo EndMT, thereby modifying their secretome and enhancing systemic inflammation (Haynes et al, 2019). ECs isolated from tumor vessels can undergo EndMT to subsequently differentiate into adipocytes, pericytes, and SMCs (Huang et al, 2015), which suggests that artificially modified EndMT-derived cells may be useful to induce tissue repair in a paracrine manner.…”
Section: Endmt In Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…Furthermore, via VE-cadherin lineage tracing in mice, EndMT was also shown to be involved in the transformation of ECs into white and brown fat cells (Tran et al, 2012). Recent manuscripts identified that microvascular ECs within adipose tissue in patients with obesity undergo EndMT, thereby modifying their secretome and enhancing systemic inflammation (Haynes et al, 2019). ECs isolated from tumor vessels can undergo EndMT to subsequently differentiate into adipocytes, pericytes, and SMCs (Huang et al, 2015), which suggests that artificially modified EndMT-derived cells may be useful to induce tissue repair in a paracrine manner.…”
Section: Endmt In Tissue Regeneration and Engineeringmentioning
confidence: 99%
“…Some groups already provide hypotheses on extracellular vesicle (EV)-mediated EMT, predominantly in the context of cancer ( 38 , 39 ), but this regulation has never been established in valve EndMT. Nevertheless, human endothelial cells that underwent EndMT secreted three-times more EVs than control endothelial cells ( 40 ). Proteomic analysis of EV content showed enrichment in inflammatory and immune-related proteins ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, human endothelial cells that underwent EndMT secreted three-times more EVs than control endothelial cells ( 40 ). Proteomic analysis of EV content showed enrichment in inflammatory and immune-related proteins ( 40 ). These results could partially explain the similar profile of biological process enrichment we observed in leaflets with a high rate of EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…Neointimal lesions exhibit shear stress-induced EndMT [ 27 ]. EndMT also contributes to maladaptive remodeling in the microvascular endothelium of obese adipose tissue (AT) in humans, leading to a loss of barrier function and angiogenic capacity [ 28 ]. In proliferative diabetic retinopathy, pathologic differentiation within the lymphatic endothelium may drive aberrant neovascularization and ischemia [ 29 ].…”
Section: Endothelial Plasticity and Heterogeneitymentioning
confidence: 99%
“…EVs obtained from adipose tissue of patients undergoing bariatric surgery were found to contain protein and miRNA cargo that reflect the proinflammatory signatures of their parent cells. These EVs have been shown to induce EndMT in adipose microvascular endothelial cells in vitro [ 28 ]. EVs derived from murine adipocyte cells exposed to the proinflammatory cytokine TNFα, induced an increase in markers consistent with EndMT in HUVECs along with increased leukocyte attachment [ 87 ].…”
Section: Extracellular Vesicles and Their Roles In Endothelial Plasticity And Heterogeneitymentioning
confidence: 99%